Microbiota-derived metabolites in regulating the development and physiology of Caenorhabditis elegans - Feng, Min; Gao, Baizhen; Garcia, L. Rene; Sun, Qing (Frontiers in Microbiology, 2023)
Microbiota consist of microorganisms that provide essential health benefits and contribute to the animal’s physiological homeostasis. Microbiota-derived metabolites are crucial mediators in regulating host development, system homeostasis, and overall fitness. In this review, by focusing on the animal model Caenorhabditis elegans, we summarize key microbial metabolites and their molecular mechanisms that affect animal development. We also provide, from a bacterial perspective, an overview of host-microbiota interaction networks used for maintaining host physiological homeostasis. Moreover, we discuss applicable methodologies for profiling new bacterial metabolites that modulate host developmental signaling pathways. Microbiota-derived metabolites have the potential to be diagnostic biomarkers for diseases, as well as promising targets for engineering therapeutic interventions against animal developmental or health-related defects.